To solve the quadratic equation \(2x^{2}-5x-3=0\), we can use the quadratic formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
where \(a = 2\), \(b = -5\), and \(c = -3\).
- First, we calculate the discriminant (\(b^2 - 4ac\)):
\[ b^2 - 4ac = (-5)^2 - 4(2)(-3) = 25 + 24 = 49 \]
- Now we can use the quadratic formula:
\[ x = \frac{-(-5) \pm \sqrt{49}}{2(2)} = \frac{5 \pm 7}{4} \]
- We find the solutions:
- For the positive case:
\[ x_1 = \frac{5 + 7}{4} = \frac{12}{4} = 3 \]
- For the negative case:
\[ x_2 = \frac{5 - 7}{4} = \frac{-2}{4} = -\frac{1}{2} \]
Thus, the solutions to the equation \(2x^{2}-5x-3=0\) are:
- \(x_1 = 3\)
- \(x_2 = -\frac{1}{2}\)
You can enter these solutions as:
- \(3\)
- \(-\frac{1}{2}\)